2019
DOI: 10.3233/adr-190137
|View full text |Cite
|
Sign up to set email alerts
|

Nature’s Derivative(s) as Alternative Anti-Alzheimer’s Disease Treatments

Abstract: Alzheimer's disease (AD), the 'Plague of Twenty-First Century,' is a crippling neurodegenerative disease that affects a majority of the older population globally. By 2050, the incidence of AD is expected to rise to 135 million, while no treatment(s) that can reverse or control the progression of AD are currently available. The treatment(s) in use are limited in their ability to manage the symptoms or slow the progression of the disease and can lead to some severe side effects. The overall care is economically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 177 publications
0
18
0
Order By: Relevance
“…In another study, 14 patients with MCI reported that a mindfulness-based stress reduction program was helpful in lowering stress levels and promoting wellbeing [ 334 ]. Meditation and mindfulness practices have also been shown to diminish release of excess cortisol and increase cerebral blood flow within the frontal lobes, a brain region that is especially important for cognitive functioning [ 335 ]. Additionally, yoga has been found to have a positive impact on biomarkers of cellular aging, presumably by regulating stress and inflammatory responses [ 336 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…In another study, 14 patients with MCI reported that a mindfulness-based stress reduction program was helpful in lowering stress levels and promoting wellbeing [ 334 ]. Meditation and mindfulness practices have also been shown to diminish release of excess cortisol and increase cerebral blood flow within the frontal lobes, a brain region that is especially important for cognitive functioning [ 335 ]. Additionally, yoga has been found to have a positive impact on biomarkers of cellular aging, presumably by regulating stress and inflammatory responses [ 336 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…Accumulation of damaging free radicals and alteration of the action of antioxidant enzymes such as superoxide catalase and dismutase are also found in AD. In AD pathogenesis, OS is an essential factor, but the causes of abnormal free radicals production and the mechanisms by which redox equilibrium is changed are not clearly understood [ 67 , 96 ]. Published research showed that abnormal aggregation of amyloid β can assist the generation of ROS via a process involving activation of NMDA receptors, and that OS can increase the development and aggregation of amyloid β along with the promotion of τ phosphorylation and polymerization, producing a vicious circle that facilitates the development and progression of AD [ 97 ].…”
Section: Pathogenesis Of Admentioning
confidence: 99%
“…Extracts of Ginkgo biloba, Olea europea and Cannabis sativa are also demonstrating strong antioxidant and immunomodulatory properties by downregulating the expression of proinflammatory cytokines such as tumor necrosis factor alpha (TNF1α), interleukin 6, interleukin 1β (IL-6, IL-1β), nuclear factor kappa B (NFκB) and stimulating neuronal autophagy and expression of autophagy-related genes [153,157,158]. It has been reported that Ginkgo extracts lower the neuronal damage in multicellular network model [159] and in animals [160].…”
Section: Natural Compounds In Treatment Of Admentioning
confidence: 99%
“…Ginkgo is widely used dietary supplement for improving cognitive functioning in healthy individuals, but also in dementia and AD, where it is often used as additional therapy with memantine [161,162]. The synergistic effects of memantine and flavonoids, terpenoids and ginkogolic acid found in Ginkgo extracts are reported to have stronger therapeutic effect than memantine alone [158,163]. Oleuropein aglycone and oleocanthal, derivatives found in olive oil, are free radical scavengers, strong inhibitors of cyclooxygenases and inhibitors of toxic protein aggregation resulting in improved cognitive performance in transgenic mice [153,157].…”
Section: Natural Compounds In Treatment Of Admentioning
confidence: 99%
See 1 more Smart Citation